GUIDANCE AND COUNSELING FAMILIES IN PERSPECTIVE HASAN LANGGULUNG - Rita Indah Yati; Ibdalsyah Ibdalsyah; Hasbi Indra (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2018)
Family is the main and foremost stone in building a country. Today there has been degradation (decrease) in divinest and sacredness of the family institution. The emergence of various problems that threaten the destruction of family ties as in the majority of today's families, such as divorce, domestic violence, sexual abuse, and drug abuse. The focus of the problem in this research is the extent to which the idea of family guidance and counseling following Hasan Langgulung complete with contributive solutions in order to establish guidance and counseling families with quality in the country. This type of research is the library research, which took the research material from several books that support research.The approach used is the approach of the literature.The main data source or object libraries are materials in the form of writings Hasan Langgulung, while secondary data are books or research results that are related to the issues studied. Based on the research results, the conclusion of thought and the concept of guidance and counseling of Hasan Langgulung family are based on the teachings of the Qur'an and the Sunnah of the Prophet, Peace Be Upon Him, where counseling is one part of the activities of da'wah and tarbiyah. Therefore, it must al-ways be oriented to direct towards the values of kindness. One aspect of the propaganda that could be acculturated, in this case the application method, between counseling and preaching is an aspect tazkiyah, especially tazkiyah al-nafs.   Keywords : Guidance, Counseling, Family